Exercise Yourself Thin : Your One-stop Guide to a Beautiful Body - Hall, Joanna (London Kyle Cathie Ltd, 2008)
Covers a range of exercises that benefit weight loss. This book focuses on improving your exercise techniques in order to help lose weight.
Include Color Illustration and Index
Keywords: Reducing exercises -- Weight loss -- Exercise for women